Trends in Antidiabetic Drug Discovery: FDA Approved Drugs, New Drugs in Clinical Trials and Global Sales - Dahlén, Amelia D.; Dashi, Giovanna; Maslov, Ivan; Attwood, Misty M.; Jonsson, Jörgen; Trukhan, Vladimir; Schiöth, Helgi B. (Frontiers in Pharmacology, 2022)
Type 2 diabetes mellitus (T2DM) continues to be a substantial medical problem due to its increasing global prevalence and because chronic hyperglycemic states are closely linked with obesity, liver disease and several cardiovascular diseases. Since the early discovery of insulin, numerous antihyperglycemic drug therapies to treat diabetes have been approved, and also discontinued, by the US Food and Drug Administration (FDA). To provide an up-to-date account of the current trends of antidiabetic pharmaceuticals, this review offers a comprehensive analysis of the main classes of antihyperglycemic compounds and their mechanisms: insulin types, biguanides, sulfonylureas, meglitinides (glinides), alpha-glucosidase inhibitors (AGIs), thiazolidinediones (TZD), incretin-dependent therapies, sodium-glucose cotransporter type 2 (SGLT2) inhibitors and combinations thereof. The number of therapeutic alternatives to treat T2DM are increasing and now there are nearly 60 drugs approved by the FDA. Beyond this there are nearly 100 additional antidiabetic agents being evaluated in clinical trials. In addition to the standard treatments of insulin therapy and metformin, there are new drug combinations, e.g., containing metformin, SGLT2 inhibitors and dipeptidyl peptidase-4 (DPP4) inhibitors, that have gained substantial use during the last decade. Furthermore, there are several interesting alternatives, such as lobeglitazone, efpeglenatide and tirzepatide, in ongoing clinical trials. Modern drugs, such as glucagon-like peptide-1 (GLP-1) receptor agonists, DPP4 inhibitors and SGLT2 inhibitors have gained popularity on the pharmaceutical market, while less expensive over the counter alternatives are increasing in developing economies. The large heterogeneity of T2DM is also creating a push towards more personalized and accessible treatments. We describe several interesting alternatives in ongoing clinical trials, which may help to achieve this in the near future.